Drying kinetics of modification cassava-seaweed noodles using an oven - Budiarti, Gita Indah; Sulistiawati, Endah; Juwitaningtyas, Titisari; Shitophyta, Lukhi Mulia; Purba, Irene Enjeli; Setiyani, Seila (International Journal of Advances in Applied Sciences, 2023)
Consumption of noodles in the world is always increasing. Noodles made from wheat flour are unhealthy because they cause diabetes, so alternative noodles are needed, such as modified cassava flour and seaweed. Modification cassava is used because it does not contain gluten and seaweed has nutritional value to make healthy, low-calorie noodles. The purpose of this study was to determine the temperature and time of the drying parameters of seaweed noodles. The drying method uses an oven with variable temperature (60, 70, 80, and 90 ) and drying time (2, 4, 6, 8, and 10 hours). The results of the study obtained optimal water content at 60  with 6 hours of 11.75%. The drying kinetics evaluated by logarithmic equation, optimal drying constant value at 80  of 0.67 h-1 with R2 0.9391. Effective moisture diffusivity (Deff) maximum evaluated by second Fick law obtained 9.35×107 m2/sec at temperature 90  with R2=0.9227. The proximate value of ash content is 12.11%, protein is 9.46%, lipid is 0.10%, and carbohydrates is 65.08%.